Home Care Service: for children with special health needs and their families (Research, Society and Development, 2022)
Objective: to describe the care process performed at home by professionals from the Home Care Service for children with special health needs and their families. Methodology: a descriptive and exploratory study, with a qualitative approach based on the theoretical/philosophical framework of the Family-Centered Care Model. Interviews were conducted with the families of children enrolled in Home Care Services in 2021. Data were analyzed using inductive thematic analysis. Results: Eight families of children with ages ranging from one to 10 years old participated, with mothers being the main caregivers. Families recognize the importance of care offered by professionals in the home service, however this is perceived in a disjointed way due to the devaluation of the families' knowledge. The health services accessed by families in the care process were identified as fragmented and disconnected from the child's needs, and not integrated into the Health Care Network. Final Considerations: it is necessary to equip the health professionals of the home care service regarding the practice that includes families in the care process; the implementation of a care model aimed at the family; the establishment of care flows in the health network; the inclusion of specialties in the teams working in the services; and strengthening families for decision-making. Such measures can contribute to solving the demands of children and their families, as well as ensuring comprehensive care.